Efficacy and Safety of Interferon Alpha 2A and Pegylated Interferon Alpha 2A in Inflammatory Macular Edema. (17th February 2020) - Couret, Chloé; Servant, Marion; Lebranchu, Pierre; Hamidou, Mohamed; Weber, Michel
ABSTRACT: Purpose : The aim of this study was to further explore the efficacy and safety of interferon-α in refractory non-infectious inflammatory macular edema and to compare interferon-α2a and pegylated interferon-α2b. Methods : 34 patients with refractory non-infectious uveitic macular edemaunder interferon-α were retrospectively reviewed. Results : Mean baseline best-corrected visual acuityimproved from 0.55 logMar to 0.37 logMAR (P < 0.001) at month (M) 1 and 0.40 logMAR (P < 0.001) at M6. The mean baseline CMT decreased from 554 µm to 367 µm (P < 0.001) at M1 and 394 µm (P < 0.001) at M6. Clinical adverse effects (AEs) were observed in a third of patients, leading to treatment discontinuation because of frequent mild AEs and few severe AE. No statistically significant difference was found between both molecules. Conclusions : Anatomically and functionally, interferon-α was rapidly effective despite a low dosage regimen and no difference in efficacy and tolerance was observed between interferon-α2a and pegylated interferon-α2b.